2021
DOI: 10.1073/pnas.2103683118
|View full text |Cite
|
Sign up to set email alerts
|

Language extinction triggers the loss of unique medicinal knowledge

Abstract: Over 30% of the 7,400 languages in the world will no longer be spoken by the end of the century. So far, however, our understanding of whether language extinction may result in the loss of linguistically unique knowledge remains limited. Here, we ask to what degree indigenous knowledge of medicinal plants is associated with individual languages and quantify how much indigenous knowledge may vanish as languages and plants go extinct. Focusing on three regions that have a high biocultural diversity, we show that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 34 publications
0
39
0
2
Order By: Relevance
“…LEK about WEP is also critical for safeguarding biocultural diversity and local resilience in times of food scarcity [ 4 , 5 ]. LEK, however, is drastically threatened by multiple factors and rapid socio-ecological changes–e.g., habitat lost, or species and language extinction [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…LEK about WEP is also critical for safeguarding biocultural diversity and local resilience in times of food scarcity [ 4 , 5 ]. LEK, however, is drastically threatened by multiple factors and rapid socio-ecological changes–e.g., habitat lost, or species and language extinction [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the potential for humans to acquire resources from nature through language will become increasingly difficult with the loss of languages. Because indigenous languages are closely related to the pharmaceutical knowledge of ethnic groups, it is believed that the demise of indigenous languages will have a greater impact on pharmaceutical knowledge than on the loss of biodiversity [ 79 ]. The use of folk botanical names enables us to harness benefits from natural plant resources.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of the socio-cultural dimension emphasizes that societies, their cultures, and nature are in constant interactions, which are integral to human survival in the biosphere [70,71]. Biodiversity and language loss have also been linked to the loss of unique medicinal plants, uses, and meanings especially among peoples who practice oral and land-based teachings [72,73]. Biocultural diversity conservation aims at sustaining the biophysical and sociocultural integrity of life systems, including the protection of species that reflect long-held relations with nature and help shape cultural identity [52,74].…”
Section: Biocultural Diversity and Plant Conservationmentioning
confidence: 99%
“…This is an issue of concern for some Haudenosaunee Peoples because in their view, a new kinship bond would need to be built between people and the new trees [93]. This illustrates that technological introductions can engender socio-cultural tensions or alter human-plant relationships that can be counterproductive to the success of plant conservation and the wellbeing of people [73].…”
Section: Biocultural Diversity and Plant Conservationmentioning
confidence: 99%